Balinanje - športna panoga - v čakalnici za priznanje olimpijskega športa - Butinar, Dušan (Šport (Ljubljana), 2016)
In year 2016 we are celebrating 65 years since bocce vole was organised in Slovenia and 25 years since Slovenia has its own national federation as member of international federation. The first competitions were held already before the second world war, however organsed federation in Slovenija was established in 1951, and today sport is expecting to became in fuure part of Olympic Games.
Keywords: achivements; balinanje; bocce vole; history; management; organiziranost; sport; šport; uspehi; zgodovina